2021
DOI: 10.3390/horticulturae7070187
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput SSR Marker Development and the Analysis of Genetic Diversity in Capsicum frutescens

Abstract: Capsicum frutescens, one of the domesticated species of pepper grown worldwide, is thought to be highly advantageous due to its strong resistance against plant pathogenesis, high productivity, and intense aroma. However, a shortage of molecular markers limits the efficiency and accuracy of genetic breeding for pepper. With the newly developed next-generation sequencing technology, genome sequences of C. frutescens can be generated, which are now available for identifying SSR markers via data mining. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…Due to these characteristics, they are the most widely recognized genetic markers actively used in plant breeding. SSR markers are widely utilized for a variety of purposes, including population genetics, functional diversity, linkage mapping, DNA fingerprinting, and most importantly, assisted breeding techniques [ 55 ]. A total of 931 numbers of hub gene sequences, which include both lncRNA and mRNA targets of miRNAs, were analyzed by the MISA tool.…”
Section: Resultsmentioning
confidence: 99%
“…Due to these characteristics, they are the most widely recognized genetic markers actively used in plant breeding. SSR markers are widely utilized for a variety of purposes, including population genetics, functional diversity, linkage mapping, DNA fingerprinting, and most importantly, assisted breeding techniques [ 55 ]. A total of 931 numbers of hub gene sequences, which include both lncRNA and mRNA targets of miRNAs, were analyzed by the MISA tool.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, Duan et al [ 47 ] investigated genetic diversity in 149 Chinese fir using the same 20 SSR markers and found these markers with high H o, H e and I values. Having high genetic parameter values for a marker is a vital indicator that the marker can be successfully used for closely related species/cultivars authentication [ 48 ]. Therefore, we propose that these loci can serve as high-resolution makers in estimation of genetic diversity and identification of inbred lines of Chinese fir.…”
Section: Resultsmentioning
confidence: 99%
“…For New Mexican germplasm, the genetic diversity of chile pepper landraces from Northern New Mexico was evaluated using random amplified polymorphic DNA ( Votava et al, 2005 ) and it was observed that the Northern New Mexico cultivars were more closely related to the Mexican varieties than the Southern New Mexican cultivars. Simple sequence repeat (SSR) markers characterized the genetic diversity of 147 C. frutescens accessions from 25 countries and clustered the population into seven major groups consistent with their geographic origins ( Zhong et al, 2021 ). In another study, SSR marker-based genetic diversity of 32 Phytophthora capsici resistant accessions of C. annuum from Ethiopia and India were evaluated and the genotypes clustered into three genetic resistance groups ( Rabuma et al, 2020 ).…”
Section: Gene Bank Collections and Genetic Diversitymentioning
confidence: 99%